Prevalensi dan Pola Gen Extended Spectrum B-lactamase Bakteri Usus Sapi Perah dan Penduduk Sekitar Peternakan di Surabaya - Imasari, Triffit; Tyasningsih, Wiwiek; Wasito, Eddy Bagus; Kuntaman, Kuntaman (Jurnal Veteriner, 2018)
Since identified in 1980s, the multiple drug resistant organisms such as Extended Spectrum Beta Lactamases (ESBL) producing bacteria is increasing. These bacteria Enterobacteriaceae strain are mostly resistant against third and also fouth generation cephalosporin. ESBL-producing bacteria are identified in both of human, environment and also in animal. There are three main ESBL genes that are commonly found namely SHV, TEM and CTX-M. The aims of this study were to explore the prevalence and pattern of ESBL gene among dairy cows and people around the farm. The faecal samples were collected from dairy cows and people around the farm, cultured on MacConkey agar supplemented with cefotaxim 1 mg/L, incubated at 37oC for 24 hours. Then the growing colony were tested for ESBL producer by Double Disk Synergy Test (DDST), then followed by Polymerase Chain Reaction (PCR) for ESBL gene. Total sampling technique with inclusion and exclusion criteria, Total 49 samples were collected, consisting of 25 dairy cows faeces and 24 people faeces. Among these, were identified 18 samples (72%) positive in dairy cows and 19 samples (79.1%) positive results in the people around the dairy farm. The ESBL gene, SHV, TEM, CTX-M were identified dairy cows were zero for SHV, TEM (12%), CTX-M (72%) while in people around the farm SHV (25%), TEM (16.7%), CTX-M (66.7%). There were significant different (p < 0.05) between dairy cows and people around the farm, of SHV ESBL gene and not different (p>0.05) of TEM and CTX-M ESBL gene respectively. The ESBL genes have spread among dairy cows and people around the farm.